Supplemental progestin increases pregnancy rates in suckled beef cows - G.C. Lamb; J.A. Cartmill; B.A. Hensley; S.E. El-Zarkouny; T.J. Marple; Jeffrey S. Stevenson; David M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2000)
In two experiments, combining a source of progestin with the ovulation synchronization protocol using gonadotropin-releasing hormone plus prostaglandin F2α (GnRH + PGF2α) tended to increase or statistically increase pregnancy rates in suckled cows compared to GnRH + PGF2α alone. These improvements were accomplished without any detected estrus when cows were inseminated and received a second injection of GnRH at 48 hr after PGF2α.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Cows; AI; Estrus-Ovulation synchronization; GnRH; PGF2α; Progestin